2013
DOI: 10.1021/ol401217h
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Oxidative Cross-Coupling of N-Tosylhydrazones with Indoles: Synthesis of N-Vinylindoles

Abstract: A general and efficient palladium-catalyzed oxidative cross-coupling reaction of N-tosylhydrazones with indoles providing N-vinylindoles has been developed. The reaction proceeds smoothly with various indoles and N-tosylhydrazones in a stereocontrolled manner, and a wide variety of N-vinylindoles were obtained up to 99% yields for 26 examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 60 publications
(18 reference statements)
0
25
0
1
Order By: Relevance
“…Other references also describe that the aryl hydrazones are an important structural unit for the transformation of alkene or alkyne to pyrazoles. We and other research groups demonstrated that tosylhydrazone have tremendous application in synthetic organic chemistry, especially in cyclization reactions. However, its reactivity toward indole has not been greatly explored. ,, Recent studies described that the reaction of tosylhydrazone with indole favors N-alkylation or N-vinylation of indole, rather than cyclization reactions with C2C3 bond (Scheme b). We hypothesized that C2–N1 bond opening could be one of the driving forces for C2C3 bond activation.…”
mentioning
confidence: 99%
“…Other references also describe that the aryl hydrazones are an important structural unit for the transformation of alkene or alkyne to pyrazoles. We and other research groups demonstrated that tosylhydrazone have tremendous application in synthetic organic chemistry, especially in cyclization reactions. However, its reactivity toward indole has not been greatly explored. ,, Recent studies described that the reaction of tosylhydrazone with indole favors N-alkylation or N-vinylation of indole, rather than cyclization reactions with C2C3 bond (Scheme b). We hypothesized that C2–N1 bond opening could be one of the driving forces for C2C3 bond activation.…”
mentioning
confidence: 99%
“…Solche Reaktionen wurden auch mit den Arylmetallspezies beobachtet, die durch eine C‐H‐Funktionalisierung mit CuI und [Cp*RhCl 2 ] 2 als Katalysator erhalten wurden. Außerdem wurde eine Insertion in die Pd‐N‐Bindung des Palladiumcarben‐Intermediats 33 vermerkt, die mit hoher Stereoselektivität N ‐vinylische Indole 32 ergab (Schema b) …”
Section: Hydrazoneunclassified
“…In 2011, Wang and co‐workers described Cu‐catalyzed coupling of N ‐tosylhydrazones with benzoxazoles and benzothiazoles via C−H functionalization . Recently, Cui′s group reported the synthesis of N ‐vinylindoles involving Pd‐catalyzed reaction of N ‐tosylhydrazones with indoles . Recently, Abdallah Hamze and his group reported the coupling of N ‐tosylhydrazones, mainly with secondary aliphatic amines and a few examples of primary amines using Cu(acac) 2 and Cs 2 CO 3 in dioxane at 100 o C for 3 h. However, under these conditions benzylation of arylamine (anisidine) using N ‐tosylhydrazone of acetophenone failed to deliver the corresponding N ‐benzylated product and generated a styrene derivative .…”
Section: Introductionmentioning
confidence: 99%